Vidro na arquitectura - Expressionismo alemão e a influência da obra de Mies Van Der Rohe, em Eduardo Souto de Moura - Marco Alexandre Peixoto Carvalho Esteves (2019)
The introduction of glass in architecture revolutionized man's way of living. The possibilities that the glass allows in construction are important factors for a good practice of architecture. The introduction of natural light and the contact with the exterior, while protecting from the atmospheric conditions that prevail outdoors are an example. This dissertation aims to contribute to the valorization of this material and to demonstrate some examples where its use is preponderant. The work of Mies van der Rohe is approached firstly due to is iconicity from the impact of glass on its buildings. In his works, both glass and steel are glazing and structure, as well as important for the refined and geometric image, that is, at the same time complex in the relations it produces. Also the expressionist movement in Germany is approached by the importance and adoration of glass and crystal. Afterwards, in the United States, Mies' architecture is discussed again, but this time inserted in the american context and in the enthusiasm generated by technology and industry. The Case Study Houses program is also studied in this chapter because of its pre-fabrication and dedication to building low-cost housing that could be built for the average citizen, trying, somehow, to bring innovation and technology to the American common user. Finally, it is discussed how this glass architecture has an impact in Portugal, and especially, in the work of Souto de Moura through three different approaches: the House of Cascais, the Enterprise Burgo and the Space Miguel Torga.